2018
DOI: 10.1002/ldr.3102
|View full text |Cite
|
Sign up to set email alerts
|

Green roofs: Effects of plant species used on runoff

Abstract: Green roofs are becoming a major nature‐based solution worldwide to reduce urban stormwater runoff. Runoff reduction and retention mainly depend on the hydrological characteristics of substrates and the water use strategies of plants. However, little is known about how plant species affect the hydrological performance of green roofs. Two commonly used succulent plants and four turfgrass species were investigated for their impacts on the hydrological performance and runoff reduction of green roof lysimeters und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 64 publications
3
13
1
Order By: Relevance
“…Speak et al [32] found that turfgrass species were more effective at PM10 capture than sedums. Our previous study also found that turfgrass species performed better in runoff reduction than sedums [9].…”
Section: Introductionmentioning
confidence: 63%
See 4 more Smart Citations
“…Speak et al [32] found that turfgrass species were more effective at PM10 capture than sedums. Our previous study also found that turfgrass species performed better in runoff reduction than sedums [9].…”
Section: Introductionmentioning
confidence: 63%
“…The centipedegrass green roof only performed 47.4% of runoff reduction under the 1487.1 mm of annual precipitation, as seen in Table 1. Runoff reduction could be promoted by the increase of water retention capacity of the green roofs [9]. The field capacity represents the maximum rainwater retention of the green roof.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations